Discrimination of Curcuma species and bioactivity correlation using NMR-based metabolomics approach and synthesis of curcumin analogs - Awin, Tahani M. (2018)
Curcuma have been widely used in traditional medicine in India and Southeast Asia to treat many human ailments including cancer, inflammation and neurodegeneration. However, there is a lack of consistency in the phytochemical profiles and biological activities of the rhizomes of Curcuma species such as C. zedoaria, C. xanthorrhiza, C. aeruginosa and C. mangga. Therefore, the aim of this study was to investigate the antioxidant, nitric oxide and α-glucosidase inhibitory properties and characterize the metabolites in selected Curcuma extracts by 1H-NMR based metabolomics approach. In the first part of the present study, rhizomes from four Curcuma species were dried using three different drying methods and extracted with two different ratios of ethanol (50% and 100%). The extracts were compared in terms of total phenolic contents (TPC), free radical scavenging (DPPH), α-glucosidase and nitric oxide inhibition. Absolute ethanol and freeze-drying were selected to process C. xanthorrhiza and C. mangga samples used in the second part of the study. The metabolite alterations at seven, eight and nine months old of C. xanthorrhiza and C. mangga were also investigated. Consequently, eight-month-old C. xanthorrhiza and nine-month-old C. mangga extracts were fractionated using solid phase extraction (SPE) to obtain nhexane, chloroform, ethyl acetate and methanol fractions. The active fractions were profiled using 1H-NMR and UPLC-DAD-ESIMS/MS analysis. Due to the richness of curcuminoids in Curcuma species, the last part of this study was focused on the synthesis of curcumin analogs. This effort was aimed to overcome the major drawbacks associated with poor solubility of curcumin.The freeze-dried C. xanthorrhiza extracted with absolute ethanol had the highest antioxidant and NO inhibitory activities, whereas the C. mangga extract with the same treatment showed the highest α-glucosidase inhibitory activity. Additionally, eightmonth- old C. xanthorrhiza exhibited the highest NO inhibitory activity, with a large quantity of curcuminoids. Nine-month-old C. mangga displayed the highest α- glucosidase inhibitory activity, with high amounts of diterpenoids. The ethyl acetate fraction from C. xanthorrhiza and C. mangga displayed the most significant bioactivities. Six curcuminoids were identified from C. xanthorrhiza and eleven compounds, including curcuminoids and diterpenoids, were identified from C. mangga. Fourteen curcumin analogs were synthesized and evaluated for their biological activity. Compounds 2, 6, 8 and 9 showed inhibitory activity against NO, with IC50 values ranging from 17 to 21 μM, and four compounds (1, 7, 13 and 14) demonstrated α-glucosidase inhibitory activity, with IC50 values ranging from 19 to 24 μM. A structure-activity relationship (SAR) study revealed that the existence of a hydroxyl substituent and a bromine group in the aromatic rings are crucial for antiinflammatory and α-glucosidase inhibitory activities. In conclusion, a 1H-NMR-based metabolomics approach is an excellent tool that can be used to monitor the quality of Curcuma species. To the best of our knowledge, this is the first study reporting on the untargeted metabolite profiling of Curcuma species using metabolomics approach. This study may support the development of Curcuma as an ingredient in medicinal preparations and as a source of food with potential in the development of nutraceutical products.